The World Bank Annual Report 2012 : Volume 2. Responding with Knowledge and Experience - World Bank (Washington, DC, 2012)
The 2012 annual report of the International Bank for Reconstruction and Development (IBRD) and the International Development Association (IDA) contains messages from both outgoing President Robert B. Zoellick and incoming President Dr. Jim Yong Kim. The Board of Directors statement highlights the Bank's achievements in 2012. The report showcases the Corporate Scorecard, presented in four tiers, providing information on the Bank's overall performance and results. Tier I provides the global development context. Tier II includes aggregate data collected through the standardized sector indicators. Tier III shows the overall success of Bank activities in achieving their development goals, as well as the Bank's operations effectiveness. Tier IV presents the Bank's organizational effectiveness and modernization. The report also discusses the financial commitments and resources, an operational summary, and World Bank lending by theme and sector for 2007-2012. Additional information on activities and outcomes is available in the annexes.